Comprehensive transcriptome analysis and functional characterization of PR-5 for its involvement in tomato Sw-7 resistance to tomato spotted wilt tospovirus - Chellappan Padmanabhan (Nature Portfolio, 2019)
Abstract Tomato spotted wilt tospovirus (TSWV), one of the most important plant viruses, causes yield losses to many crops including tomato. The current disease management for TSWV is based mainly on breeding tomato cultivars containing the Sw-5 locus. Unfortunately, several Sw-5 resistance-breaking strains of TSWV have been identified. Sw-7 is an alternative locus conferring resistance to a broad range of TSWV strains. In an effort to uncover gene networks that are associated with the Sw-7 resistance, we performed a comparative transcriptome profiling and gene expression analysis between a nearly-isogenic Sw-7 line and its susceptible recurrent parent (Fla. 8059) upon infection by TSWV. A total of 1,244 differentially expressed genes were identified throughout a disease progression process involving networks of host resistance genes, RNA silencing/antiviral defense genes, and crucial transcriptional and translational regulators. Notable induced genes in Sw-7 include those involved in callose accumulation, lignin deposition, proteolysis process, transcriptional activation/repression, and phosphorylation. Finally, we investigated potential involvement of PR-5 in the Sw-7 resistance. Interestingly, PR-5 overexpressed plants conferred enhanced resistance, resulting in delay in virus accumulation and symptom expression. These findings will facilitate breeding and genetic engineering efforts to incorporate this new source of resistance in tomato for protection against TSWV.